2011
DOI: 10.1016/j.sjbs.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of drought stress of marigold (Tagetes erecta) plants by using arbuscular mycorrhizal fungi

Abstract: The effect of an arbuscular mycorrhizal fungus "AMF" (Glomus constrictum Trappe) on growth, pigments, and phosphorous content of marigold (Tagetes erecta) plant grown under different levels of drought stress was investigated. The applied drought stress levels reduced growth vigor (i.e. plant height, shoot dry weight, flower diameter as well as its fresh and dry weights) of mycorrhizal and non-mycorrhizal plant as compared to control plant (non-drought stressed plant). The presence of mycorrhizal fungus, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 30 publications
13
62
0
Order By: Relevance
“…In addition to plant growth, AMF also help plants to withstand various environmental stress including salinity (Abdel Latef and Chaoxing 2011;Navarro et al, 2012), drought (Asrar and Elhindi 2011) and protects plant from pathogen attack (Nair et al, 2014). Hajiboland et al (2010) reported that the mycorrhizal inoculation increased tomato plant growth at 5 dS m -1 salinity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to plant growth, AMF also help plants to withstand various environmental stress including salinity (Abdel Latef and Chaoxing 2011;Navarro et al, 2012), drought (Asrar and Elhindi 2011) and protects plant from pathogen attack (Nair et al, 2014). Hajiboland et al (2010) reported that the mycorrhizal inoculation increased tomato plant growth at 5 dS m -1 salinity.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the AM effect on carotenoid is more important in Mg-D than in Mg-S. In fact, carotenoids can protect photosynthetic apparatus against oxidative damage, as well quench excited triple state of chlorophyll in plants (Asrar and Elhindi, 2011.). Xiao et al (2014) confirmed greater photosynthesis of Newhall and Ponkan seedlings inoculated with Glomus versiforme under Mg-D conditions.…”
Section: Chlorophyll Concentrationsmentioning
confidence: 89%
“…These changes induced various effects on growth and yield parameters of the crops (Reisdorph & Koster, 1999). Many studies showed inhibitory effects of drought stress on different plant properties, such as grain yield in maize (Ebrahimian & Bybordi, 2011); growth and productivity in sunflower, fresh and dry weights in shoot and flowers of marigold (Tagetes erecta L.) and Asian red sage (Asrar & Elhindi, 2011;Liu et al, 2011) and yield reduction due to limited growth in bread wheat (Abbas et al, 2009). In soybean, biological nitrogen fixation carried out by bacterium Bradyrhizobium sps., it was reported that drought condition adversely affect the biological nitrogen fixation in this crop.…”
Section: Introductionmentioning
confidence: 99%